1997
DOI: 10.1029/97gl01849
|View full text |Cite
|
Sign up to set email alerts
|

Geocenter variations caused by atmosphere, ocean and surface ground water

Abstract: remains static in an inertial frame. Without loss of generality we define an inertial frame (CM frame) with CM as its origin and let the CM, CE and CF coincide before mass redistribution. In CM frame, the coordinates of CE, CF and mass load are denoted as rCE, rCF and rload respectively. We define the coordinates of CF and mass load in an Earth-fixed reference frame (CE frame) with CE as its origin as rCF and rload. There are simple geometric and mass balance relations rload = rCE + rload, rCF = rCE + rCF (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 11 publications
5
116
0
Order By: Relevance
“…Apparent seasonal fluctuations between the center of mass and geocenter observed using SLR have peak-to-peak amplitudes of -40 mm, but such fluctuations average to a velocity insignificantly different from zero Eanes, 1993, 1997;Kar, 1997]. Seasonal fluctuations caused by observed variations in the atmosphere, the oceans, and the Earth's groundwater have peakto-peak amplitudes of-5 mm and average to a velocity of less than 1 mm/yr [Dong et al, 1997]. The current offset between the center of mass and the geocenter can be calculated using the spherical harmonic coefficients of Pavlis and Rapp [1990]: the geocenter is 1.2 km nearer the surface location 46øN, 34øE than the center of mass.…”
Section: Rebound-adjusted Geocenter Equals Center Of Mass (Rag=cm)mentioning
confidence: 99%
“…Apparent seasonal fluctuations between the center of mass and geocenter observed using SLR have peak-to-peak amplitudes of -40 mm, but such fluctuations average to a velocity insignificantly different from zero Eanes, 1993, 1997;Kar, 1997]. Seasonal fluctuations caused by observed variations in the atmosphere, the oceans, and the Earth's groundwater have peakto-peak amplitudes of-5 mm and average to a velocity of less than 1 mm/yr [Dong et al, 1997]. The current offset between the center of mass and the geocenter can be calculated using the spherical harmonic coefficients of Pavlis and Rapp [1990]: the geocenter is 1.2 km nearer the surface location 46øN, 34øE than the center of mass.…”
Section: Rebound-adjusted Geocenter Equals Center Of Mass (Rag=cm)mentioning
confidence: 99%
“…They concluded that the amplitudes of geocenter variations introduced by geophysical fluids (air and water) were less than I cm, about the same magnitude as the observed geocenter motions [Dong et al, 1997].…”
mentioning
confidence: 97%
“…[20] Global groundwater variations are expected to dominate the variations of the geocenter [Dong et al, 1997]. In this study, we ignored possible contribution (for all degrees) due to atmospheric loading, the next-largest contributor, and this approach may contribute to the 1.5 mm (RMS) GRACE-GPS disagreement.…”
Section: Componentmentioning
confidence: 99%